Metasystems : how trust can change the world - Van Peteghem, Dado, ....-; Van Dam, Nils, ....- (Brugge : Die Keure, 2020)
In the past 30 years, technology has caused waves of disruptive developments, each crashing onto society and business alike. With the tide building and the pace accelerating, the next wave promises to come in big. These new challenges have a societal and environmental impact, are systemic and increasingly complex. Our old ways of doing business don't suffice anymore. Furthermore, the future is too fast and too complex to go at it alone. In the future, competition will happen on the level of ecosystems, not just on the level of companies, products or services. This book gives companies the tools to build mutually beneficial, equal and sincere partnerships. We call them metasystems. And we believe them to be the most suitable armor for the next decade. Metasystems are built on trust and purpose. The biggest challenge is how to leverage the soft side, the human factor again.